2013
DOI: 10.1371/journal.pone.0076224
|View full text |Cite
|
Sign up to set email alerts
|

A Cocktail of Thermally Stable, Chemically Synthesized Capture Agents for the Efficient Detection of Anti-Gp41 Antibodies from Human Sera

Abstract: We report on a method to improve in vitro diagnostic assays that detect immune response, with specific application to HIV-1. The inherent polyclonal diversity of the humoral immune response was addressed by using sequential in situ click chemistry to develop a cocktail of peptide-based capture agents, the components of which were raised against different, representative anti-HIV antibodies that bind to a conserved epitope of the HIV-1 envelope protein gp41. The cocktail was used to detect anti-HIV-1 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Indeed, the PCC agents developed against this epitope exhibit both inhibitory and activating characteristics depending upon the PCC agent structure. Additional advantages relative to the mAb include the well‐defined chemical structure of the PCC agents developed, as well as their stability against proteases and physical stresses 27. Delivery of these or similarly targeted ligands into live cells to explore their potential as therapeutic inhibitors of Akt2 is under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the PCC agents developed against this epitope exhibit both inhibitory and activating characteristics depending upon the PCC agent structure. Additional advantages relative to the mAb include the well‐defined chemical structure of the PCC agents developed, as well as their stability against proteases and physical stresses 27. Delivery of these or similarly targeted ligands into live cells to explore their potential as therapeutic inhibitors of Akt2 is under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that tetraphenylethylene (TPE) clicked with a fluorescent 6′sialyllactose moiety can be used as a "turn-on" fluorescent sensor to detect the influenza virus (Kato et al, 2010). A cocktail of thermally stable capture agents generated using click chemistry can be used to detect the anti-gp41 antibodies of HIV-1 from human sera with high sensitivity and specificity (Pfeilsticker et al, 2013). To increase the sensitivity of the biosensor, a variable domain of llama heavy-chain antibodies, which can specifically recognize the foot-and-mouth disease virus, was clicked with azides to generate bioorthogonal reactive groups (Trilling et al, 2014).…”
Section: Diagnosis Of Viral Infectionmentioning
confidence: 99%
“…Additional advantages relative to the mAb include the well-defined chemical structure of the PCC agents developed, as well as their stability against proteases and physical stresses. [27] Delivery of these or similarly targeted ligands into live cells to explore their potential as therapeutic inhibitors of Akt2 is under investigation.…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%